Von Brüchen und Brücken. Sprachliche Bildung im Übergang von der Kita zur Schule - Albers, Timm (Jugendhilfereport)

Erbwort oder Buchwort? Decoding the Disciplines in Romanistikseminaren - Kunert, Irene Dorothea (die hochschullehre)

Umgang mit digitalen Medien im Jugendalter - Kurock, Ricarda; Jungkeim, Lisa; Kuhn, Nicole (Handbuch Entwicklungs- und Erziehungspsychologie)
Das Kapitel beleuchtet, wie digitale Medien von Jugendlichen genutzt werden und wie diese Nutzung die Entwicklung von Jugendlichen beeinflusst, indem Einblicke in Nutzungsmuster, Chancen und Risiken digitaler Medien sowie in den Stand digitaler Kompetenzen gegeben werden. Zwei zentrale Sozialisationsinstanzen (Familie und Peers) werden genauer beleuchtet. Ziel ist es, pädagogische und gesellschaftliche Strategien zur Förderung digitaler Mündigkeit aufzuzeigen.
Keywords: Mediennutzung; Soziale Medien; Digitale Kompetenzen; Peers; Familie

Aging of polyurethane foam: Experimental analysis and modeling of cell gas composition and thermal conductivity - Schumacher, Daniel; Guevara-Carrion, Gabriela; Kasper, Tina; Paul, Andreas; Elsner, Andreas; Peters, Bettina; Wollny, Wenke; Bluemel, Marcus; Hoelscher, Heike; Brzoska-Steinhaus, Nicola; Heil, Klaus; Schleelein, Lukas; et al. (Applied Thermal Engineering)
The aging behavior of closed-cell polyurethane (PUR) foam, a material widely used in household refrigeration, is studied by examining the variation of cell gas composition and thermal conductivity over time. Aging is primarily driven by gas permeation, wherein the initially present cell gases carbon dioxide and cyclopentane are progressively replaced by nitrogen and oxygen from the ambient, resulting in an increased thermal conductivity and reduced insulation performance. The cell gas composition is measured over 1400 days employing gas chromatography, and the thermal conductivity of the foam is measured over 190 days. Morphological foam characteristics, such as average cell diameter, are determined via scanning electron microscopy and barrier measurements are performed to estimate the effective diffusion coefficient of oxygen. To simulate the aging process, one-dimensional and three-dimensional models are developed for both diffusive mass transfer as well as heat transfer. The present model for the thermal conductivity explicitly accounts for condensation effects, i.e. partial condensation of cyclopentane and carbon dioxide occurring at around 12°C, which significantly influences the insulation behavior of the foam. Sensitivity analyses indicate that an initial cell gas pressure of approximately 0.7 bar yields results that closely coincide with the experimental measurements, where the three-dimensional model demonstrates better accuracy. These measurements and simulations provide valuable insights for evaluating and predicting the long-term degradation of the insulation performance of PUR foams.
Keywords: Polyurethane; Foam; Gas permeation; Diffusion models; Thermal conductivity; Condensation; Gas chromatography; Scanning electron microscopy

Nachhaltiges Clubsterben? Überlegungen zu Kommodifizierung und Nachhaltigkeit im Kontext des Clubsterbens in Deutschland (im Erscheinen) - Flath, Beate (Clubsterben: Sozioökonomischer Wandel und urbane Musikkulturen)

Livemusikkulturen, Virtualitäten und Metamorphosen: Perspektiven auf das kulturökonomische Konzept der Baumol’schen Kostenkrankheit - Flath, Beate (~Vibes - The IASPM D-A-CH Series)

Comparative Theology and Social Work: Exploring Theory and Praxis in Pluralistic Societies
This volume presents insights from the 2025 ITS-Colloquium on Comparative Theology and So-cial Work, exploring how theological concepts and interreligious dialogue inform and critically engage social practice. Drawing on insights from education, psychosocial support, military chaplaincy, and community-building, it reveals the transformative potential of comparative theology in addressing migration, marginalization, and social fragmentation. The contributions critically examine the ethical depth and practical challenges of integrating religious perspectives into social work, offering valuable insights for theory and praxis in pluralistic societies, while also showing the limits and challenges of theoretical models. Overall, when critically and contextually applied, impulses from comparative theology offer both conceptual depth and practical tools for ethical, inclusive, and transformative social engagement.

An Axiomatization of the Banzhaf Index to Measure Influence in Qualitative Comparative Analysis - Haake, Claus-Jochen; Schneider, Martin (International Journal of Game Theory)
The Banzhaf power index can be used to quantify the explanatory power of single conditions in a configurational analysis that aims at identifying whether combinations of conditions are sufficient for an outcome. The latter method is an integral part of the Qualitative Comparative Analysis (QCA) approach. It is widely used in the literature, e.g., in the field of International Management. Haake and Schneider (2023) give a rigorous description of the connection between the empirical and game theoretic modeling. To justify that the Banzhaf index is an appropriate tool to measure the influence of a condition, this paper discusses a novel axiomatization of the Banzhaf index that uses axioms that are directly linked to the QCA methodology. As a side result, we demonstrate that in our model the Banzhaf index can be reinterpreted as an average of Shapley-Shubik indices.
Keywords: Banzhaf index; axiomatization; QCA; explanatory power

„Mind the gap“: Mentoring für Frauen in der Statuspassage Studium – Promotion - Steinhausen, Julia (Praxishandbuch Mentoring in der Wissenschaft)
Keywords: Mentoring; Frauen; Wissenschaft

Wo Forschung, KI und Praxis aufeinandertreffen - Trienens, Dorte; Brüning, Florian; Schöppner, Volker (kunststoffland NRW report)

Transitionen von Kindern mit erschwerten Lern- und Teilhabevoraussetzungen begleiten - Schlesier, Juliane; Rank, Astrid; Then, Daniel; Pohlmann-Rother, Sanna; Herding, Jana; Büker, Petra; Carle, Ursula (Bezugsnotwendigkeiten in der Grundschule. Pädagogik und Fachdidaktik in der Grundschulbildung)

Motive Ingenieurstudierender für den Besuch (fach-)didaktischer Lehrveranstaltungen im Projekt EduTech Net OWL - Vernholz, Mats; Temmen, Katrin (die hochschullehre)

Using Google’s Natural Language Model to Measure Growth of Knowledge in Information Systems Research - Hassan, Nik; Marrone, Mauricio; Schryen, Guido; Yang, Jack (Proceedings of the 59th Hawaii International Conference on System Sciences)

A modified Levenberg–Marquardt method for estimating the elastic material parameters of polymer waveguides using residuals between autocorrelated frequency responses - Itner, Dominik; Dreiling, Dmitrij; Gravenkamp, Hauke; Henning, Bernd; Birk, Carolin (Mechanical Systems and Signal Processing)
In this contribution, we address the estimation of the frequency-dependent elastic parameters of polymers in the ultrasound range, which is formulated as an inverse problem. This inverse problem is implemented as a nonlinear regression-type optimization problem, in which the simulation signals are fitted to the measurement signals. These signals consist of displacement responses in waveguides, focusing on hollow cylindrical geometries to enhance the simulation efficiency. To accelerate the optimization and reduce the number of model evaluations and wait times, we propose two novel methods. First, we introduce an adaptation of the Levenberg–Marquardt method derived from a geometrical interpretation of the least-squares optimization problem. Second, we introduce an improved objective function based on the autocorrelated envelopes of the measurement and simulation signals. Given that this study primarily relies on simulation data to quantify optimization convergence, we aggregate the expected ranges of realistic material parameters and derive their distributions to ensure the reproducibility of optimizations with proper measurements. We demonstrate the effectiveness of our objective function modification and step adaptation for various materials with isotropic material symmetry by comparing them with the Broyden–Fletcher–Goldfarb–Shanno method. In all cases, our method reduces the total number of model evaluations, thereby shortening the time to identify the material parameters.
Keywords: Material parameter estimation; Waveguide; Nonlinear optimization; Inverse problem; Least squares

Approximating Incoherent Monochromatic Light Sources in FDTD Simulations - Metzner, Dominik; Potthoff, Jens; Zentgraf, Thomas; Förstner, Jens (Photonics)
Light-emitting diodes (LEDs) are becoming increasingly important across various sectors of the lighting industry and are being used more frequently. In the field of symbolic projection, research is increasingly focusing on implementing light modulation using energy-efficient, incoherent LEDs rather than lasers. Since light modulation in micro- and nano-optics is typically achieved through phase modulation, Finite-Difference Time-Domain (FDTD) simulations are employed for analysis. The objective of this article is to investigate different approaches for approximating incoherent monochromatic light sources within FDTD simulations. To this end, two approaches based on dipole sources are considered, as well as a method involving plane waves with modulated wavefronts based on Cosine–Fourier functions and a method based on the superposition of Gaussian beams. These methods are evaluated in terms of their accuracy using a two-dimensional double-slit configuration and are compared against a fully incoherent analytical reference.
Keywords: tet_topic_opticalantenna; tet_topic_numerics; tet_topic_meta

Rules and Reasoning - 9th International Joint Conference, RuleML+RR 2025, Istanbul, Turkey, September 22-24, 2025, Proceedings

From Engineering to Shaping: A Multiple Case Study on Advancing Service Systems Engineering through Continuous Value Shaping - Schäfer, Jannika Marie; Rajko, Polina; Angelova, Daniela; Böhmann, Tilo (Proceedings of the 59th Hawaii International Conference on System Sciences (HICSS 2026))
Service systems engineering relies on structured, top-down approaches to designing and innovating service systems. In today’s dynamic environments—shaped by digital transformation, evolving provider–user interactions, and shifting societal demands—these approaches face limitations in enabling continuous, context-sensitive innovation. Continuous Value Shaping emerges as a conceptual extension to service systems engineering, promoting more adaptive and co-evolutionary forms of service system development. This study examines how Continuous Value Shaping manifests through a multiple case study of three public sector projects. We identify distinct manifestations and constellations of the concept’s principles that complement classical SSE practices. As the first empirical exploration of Continuous Value Shaping, the study refines its conceptual foundation and enhances its accessibility for researchers and practitioners. We conclude with seven empirically derived propositions that inform future service systems engineering initiatives and demonstrate how Continuous Value Shaping supports the dynamic alignment of service systems with societal and systemic demands.
Keywords: Continuous Value Shaping; Service Systems Engineering; Service Science; Public Sector; Service Innovation

Children and adolescents with psychiatric disorders have high relative leptin levels upon adjustment for sex, BMI, and pubertal status - Albers, Nicola; Antel, Jochen; Föcker, Manuel; Libuda, Lars; Bühlmeier, Judith; Hirtz, Raphael; Seitz, Jochen; Hinney, Anke; Hebebrand, Johannes; Peters, Triinu (European Child & Adolescent Psychiatry)
Abstract The relationship between leptin levels and psychiatric disorders has been studied more extensively in adults than in children and adolescents. However, the results are conflicting. We investigated serum leptin levels in children and adolescents (11 to 18.9 years) with psychiatric disorders ( n = 363). Absolute and relative (body-mass-index (BMI)-, sex- and pubertal-stage-adjusted z-scores using reference values of healthy children and adolescents) leptin levels of different patient groups according to diagnosis were compared. The association between leptin levels and depression (Beck Depression Inventory-II) and anxiety (Child Behavior Checklist and Youth Self Report) was examined using regression analysis. Leptin z-scores were higher in patients with psychiatric disorders than in healthy controls (median 1.50, p < .001). While global tests suggested differences in leptin z-scores between patients with different psychiatric disorders, these differences could not be attributed to diagnosis groups in post-hoc pairwise comparisons. Absolute leptin levels differed between psychiatric disorders ( p < .001). Patients with anorexia nervosa (AN) had the lowest levels, and patients with mood disorders had higher leptin levels than patients with mental disorders other than mood disorders, anxiety or AN. Neither absolute nor relative leptin levels were related to depressive or anxiety symptoms in regression models adjusted for sex and BMI. Significantly elevated BMI-, sex- and puberty-stage-adjusted leptin levels were observed in children and adolescents with psychiatric disorders compared to a reference sample. Further controlled studies are needed to confirm and explain this finding. No relationship was found between absolute or relative leptin levels and symptoms of depression or anxiety.

Adherence to dietary recommendations according to the General Dietary Behavior Inventory (GDBI) and its association with bioelectrical impedance analysis (BIA) parameters among young, healthy and normal weight women - Knoll-Pientka, Nadja; Schils, Dorina; Mantwill, Katrin; Dinse, Hannah; Skoda, Eva-Maria; Bäuerle, Alexander; Teufel, Martin; Libuda, Lars (BMC Nutrition)

Proton-Conducting Sulfonated Periodic Mesoporous Organosilica - Wagner, Tobias; Tiemann, Michael (Nanomaterials)
Proton exchange membranes (PEMs) are essential for fuel cells, yet conventional materials like Nafion suffer from humidity dependence and limited thermal stability. This study introduces sulfonated phenylene-bridged periodic mesoporous organosilicas (PMOs) as promising inorganic–organic hybrid PEMs, synthesized via surfactant-templating with varying alkyl chain lengths for different mesopore sizes. Post-synthetic functionalization involves nitration of phenylene moieties, reduction to amines, and ring-opening of propane or butane sultones to graft sulfonic acid groups via flexible spacers, achieving homogeneous distribution along pore walls. Post-functionalization is confirmed by powder X-ray diffraction (PXRD), revealing preserved 2D hexagonal p6mm ordering and phenylene stacking. N2 physisorption shows type IV isotherms with reduced pore volumes and pore sizes. 1H NMR is used to quantify functionalization degrees. Impedance spectroscopy on pressed pellets demonstrates proton conductivities up to 2 × 10−3 S cm−1 at 30 °C and 90% RH, depending on the functionalization degree, confirming sulfonic acid-mediated conduction.